The Risks of Globalization on Youth and the Role of Social Work in Addressing Them (Journal of human and social sciences, 2022)
The phenomenon of globalization has reshaped the world into a “global village,” eliminating traditional boundaries in geography economy, social structures, and cultural practices through advancements in communication and information technology. While globalization offers many advantages in technology, industry, knowledge exchange, and human rights, it also poses significant challenges, particularly for youth. Young people, as the most frequent users of modern technologies, are highly exposed to cultural and social influences that may threaten national identity, values, and social cohesion. This study examines the risks globalization imposes on youth—such as cultural alienation, identity loss, unemployment, crime, and social disintegration—and explores the role of social work in mitigating these risks. Using a descriptive analytical approach, the study reviews literature on globalization, its social and cultural impacts on youth, and the potential contributions of social work in promoting resilience, strengthening social values, and addressing youth-related issues. The research aims to identify the nature and scope of globalization, highlight its negative effects on youth, and emphasize how social work can serve as a vital tool to safeguard cultural identity, enhance social responsibility, and support the developmental role of youth as the backbone of society.
Keywords: Globalization; Social Work; Youth; Cultural Identity; Social Challenges